Natural disasters and community resilience: the case of El Morro, Chile - Moreno Romero, Jenny Andrea (2016)
The purpose of this study is to analyse the impact of the 2010 Chile earthquake and tsunami on community resilience. Specifically, the thesis examines the role of community resilience in coping with and recovery from natural disasters, and the capacities and external factors that enhance or undermine the levels of community resilience. Furthermore, this study focuses on developing a model suitable for analysing community resilience in the context of natural disasters in Chile. In 2010, a magnitude 8.8 earthquake and tsunami struck Chile. Coastal areas were particularly affected by the disaster; fishing villages were completely destroyed and many people were injured and killed by the tsunami. However, exceptionally, only one fishing village entirely survived the tsunami impact in Talcahuano, one of the worst affected regions by the disaster. This is the case of the ‘El Morro’ community where, despite their boats and houses being swept away by the destructive waves, no one died. This community, considered the most successful experience in coping effectively with the disaster in the country, is the case analysed in this thesis. The results of a primary research conducted in the ‘El Morro’ case study (through methods of semi-structured interviews, observation, informal conversations, documentary review and social media) show that communities have the power to activate internal resources and capacities to cope with and recover from natural disasters. The research highlights that communities are not simply passive victims of disasters; rather, they are active agents. Furthermore, it shows that external factors, specifically political ones can have a detrimental effect on community resilience. Additionally, an integrated model of community resilience was developed which provides new insights into measuring community resilience in the context of natural disasters. Finally, these findings could be useful for designing effective disaster risk reduction programmes and promoting community resilience in Chile and in other developing countries.